Histopathological analysis of liver of the catfish Pimelodus maculatus in a tropical eutrophic reservoir from Southeastern Brazil - Araujo, Francisco Gerson (2019)
We described liver tissues of the long-whiskered catfish Pimelodus maculatus using histological techniques through structures stained with hematoxylin and eosin. The main aim was characterize the tissues and eventual changes, since this organ has a notable sensitivity to change in altered aquatic systems. The liver has a parenchyma divided into irregular lobules containing the exocrine pancreas (hepatopancreas) that have pancreatic cells arranged around a branch of the portal vein. The hepatocytes are diffuse and arranged in cords. The organization of exocrine pancreatic tissues is similar to the acinar morphology of many teleosts. Six types of liver alterations were found: 1) cytoplasmic vacuolization; 2) congestion; 3) inflammatory infiltrated; 4) infiltration of adipocytes; 5) steatosis; 6) cytoplasmic granules. Incidence of melano-macrophage centers were observed in the liver, suggesting an immune response to contaminants. However, we cannot associate directly such changes with the eutrophic conditions of the reservoir because we have no available reference area to compare. These findings are baseline contribution that enable comparisons with similar fish species in other tropical aquatic systems in further studies